Climate laws and green finance: The value of legal commitment - Gabriele Ciminelli; Filippo Maria D'Arcangelo; Mauro Pisu; Shu Tian (Asian Development Bank (ADB), 2025)
Using newly compiled cross-economy data on national climate legislation matched with mutual fund portfolio holdings, this paper finds that enshrining a climate commitment in law redirects capital toward green assets. A staggered difference-in-differences design reveals that legally binding climate commitments lead to a substantial increase in the share of environmental, social, and governance (ESG) holdings in total mutual fund assets. The effect is driven by laws setting net-zero emission reduction targets, which increase the ESG share by about 5 percentage points over 5 years. A simple back-of-the-envelope calculation suggests this corresponds to a rise in ESG mutual funds' holdings of about 1.8% of gross domestic product. The effect, which is strongest in bond and actively managed funds, is explained by tighter mitigation policies as well as reduced policy uncertainty and reflects an expansion in both the supply of and demand for green assets, rather than asset price changes. These findings underscore the role of legally binding commitments in anchoring expectations and mobilizing climate finance.
Keywords: G11; G15; G18; Q54; Q58; 330; climate laws; net-zero targets; sustainable finance; ESG investment; mutual funds; policy uncertainty; climate policy stringency